Assessment of combining ability with elite genotypes in sesame (Sesamum indicum L.) by half diallel mating design: Assessment of combining ability with elite genotypes in sesame (Sesamum indicum L.) by half diallel mating design - S J SONAWANE; P B WADIKAR; ANJALI TALAPE (Journal of Oilseeds Research, 2020)
The present investigation was undertaken with the objective of studying the extent of heterosis and to estimategeneral and specific combining ability effects in 28 hybrids of sesamum obtained by crossing 8 x 8 genotypes in half diallel fashion. The analysis of variance revealed that significant differences among treatments, parents, hybrids and parents v/s hybrids for all characters except days to maturity and capsule width. Among parents, LOCAL and G-1 was good general combiners for seed yield/plant. Considering both per se and GCA effect, the parents LOCAL and AKT306 were the best. The highest SCA effect for seed yield/plant was exhibited by cross G-1 x IC-204025 along with superior SCA effect for plant height, number capsule/plant and seed/capsule. The crosses AKT-306 x YLM-17 and LOCAL x AKT-101 with significant SCA effects indicated the predominace of additive gene action for seed yield hence progeny selection in the segregating generation is more useful.